Respuesta :

Answer:

[2]    x = -5y - 4

// Plug this in for variable  x  in equation [1]

  [1]    2•(-5y-4) - 5y = 22

  [1]     - 15y = 30

// Solve equation [1] for the variable  y

  [1]    15y = - 30

  [1]    y = - 2

// By now we know this much :

   x = -5y-4

   y = -2

// Use the  y  value to solve for  x

   x = -5(-2)-4 = 6

Solution :

{x,y} = {6,-2}

  Processing ends successfully  

Subscribe to our mailing list

Email Address

Terms and Topics

Linear Equations with Two Unknowns

Solving Linear Equations by Substitution

Related Links

Algebra - Linear Systems with Two Variables

Step-by-step explanation:

They are correct!!!!